2017
DOI: 10.1002/jsfa.8724
|View full text |Cite
|
Sign up to set email alerts
|

Association between the gut microbiota and mineral metabolism

Abstract: The aim of this review is to present the most recent scientific evidence of interactions between the intestinal microbiota and minerals, and the effect of this interaction on the health of the host. The Web of Science database from the years 2013-2017 on this topic was reviewed. Numerous in vitro studies have shown that iron significantly affects the intestinal microbiota. However, Bifidobacteriaceae are capable of binding iron in the large intestine, thereby limiting the formation of free radicals synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 94 publications
1
89
1
Order By: Relevance
“…[272][273][274][275] Different bacterial taxa modulate immune functionality toward a pro or antiinflammatory pattern, extensively summarized previously. [276][277][278] Thus, the composition of the microbiota community determines, in part, the level of resistance to infection and susceptibility to inflammatory diseases.…”
Section: Zinc and The Microbiomementioning
confidence: 99%
“…[272][273][274][275] Different bacterial taxa modulate immune functionality toward a pro or antiinflammatory pattern, extensively summarized previously. [276][277][278] Thus, the composition of the microbiota community determines, in part, the level of resistance to infection and susceptibility to inflammatory diseases.…”
Section: Zinc and The Microbiomementioning
confidence: 99%
“…2 The intestinal microbiota has a wide variety of functions, and one of the best explored is its immune function. 9 A positive independent influence of probiotics on serum triglyceride concentration and liver mass has been reported, exerting a favorable and dose-dependent effect on liver function and lipid profile in the rat model and possibly also have a favorable influence on cardiovascular impairment. 10 Yesilbag et al 11 demonstrated that juniper essential oil supplements had a significant impact on children's antioxidant blood parameters.…”
Section: Introductionmentioning
confidence: 99%
“…First, minerals may play an important role in intestinal probiotics as they are responsible for obtaining energy for gut bacteria. 61 Importantly, recent studies have confirmed that some minerals have prebiotic activities. Calcium favorably changes the intestinal flora through the precipitation of bile acids and reduction in fatty acids, resulting in increased probiotic density and activity.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the prebiotic potential of Carapax Trionycis might be explained as follows. First, minerals may play an important role in intestinal probiotics as they are responsible for obtaining energy for gut bacteria . Importantly, recent studies have confirmed that some minerals have prebiotic activities.…”
Section: Discussionmentioning
confidence: 99%